Incomes policies: Two approaches - Claudio Sardoni (Intervention. European Journal of Economics and Economic Policies, 2011)
Post-Keynesians in general, and Geoff Harcourt in particular, have always laid much emphasis on incomes policies, which allow policy-makers to implement expansionary demand-side policies and ensure price stability. Mainstream economics, instead, gives little, if any, relevance to incomes policies. The central bank's monetary policy is the main tool to be used to ensure price stability. In the mainstream approach, price stability is ensured by constraining the economy's level of output and employment below full employment. This can be defined as the mainstream implicit incomes policy. This article argues that policy indications different from the mainstream can be derived. This, in particular, is done by removing the typical hypothesis that, in the short period, productivity is constant and independent of variations of aggregate output. This sort of approach allows for non-inflationary demand expansionary policies, which at the same time can promote the productivity and efficiency of the economy as a whole. This line of analysis is largely influenced by the work of Geoff Harcourt.
Keywords: E10; E12; E64; O4; 330; incomes policy; incomes distribution; mainstream macroeconomics; Post Keynesian macroeconomics